TITIK SINGGUNG WEWENANG ANTARA MA DAN MK - MD, Moh Mahfud (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2015)
The existence of the Constitutional Court (MK) in Indonesia is linked to the Supreme Court (MA) both in the universal philosophy and in history and the particular debate. Being natural in practice found several points of authority tangency which must be resolved not only academically but in juridiction. If powers of the Constitutional Court was elaborated and then linked with the authority of the Supreme Court the authority then it appears there is a cross between the two institutions. The Constitutional Court judge rules conflict which is abstract at once judges conflicts (disputes) between the person or institution that is concrete. There is also the Supreme Court also adjudicates conflicts (disputes) between people or institution that is concrete as well adjudicates conflicts between rules which are abstract. Here appears the cross testing authority in legislation between the Constitutional Court and the Supreme Court because they both have the authority to conduct testing, but to different degrees.Keywords: Connective Point, Supreme Court, Constitutional Court